Perfectionism and fear of failure, according to sporting experience. A referee handball study - Gómez-López, Manuel; Manzano-Sánchez, David; Borrego, Carla Chicau; González-Hernández, Juan (Frontiers in Psychology, 2025)
IntroductionFear of failure is a motive to avoid failure in evaluative situations based on anticipatory shame upon failure. Perfectionism is a personality disposition characterized by striving for flawlessness and setting exceedingly high standards of performance accompanied by overly critical evaluations of one’s behavior. The goal of the study was to describe the effects of previous sports experiences that handball referees had, related to perfectionism and fear of making mistakes.MethodsData were collected from 120 referees (93 males, 77.5%; 27 females, 22.5%), ranging in age from 14 to 62 years (M = 28.12; SD = 11.99), using purposive sampling methods. The Performance Failure Assessment Inventory and the Multidimensional Inventory of Perfectionism in Sport were used. Data were analyzed using differential, correlational and regression analysis.ResultsResults showed that both perfectionistic tendencies and fear of failure provide interaction effects on fear of failure. Differences in perfectionist tendencies according to gender (women) and in favor of referees who were coaches or handball players before becoming referees.DiscussionInterventions can be developed to help reduce Fear of Failure and Perfectionism.